(untitled) (Bangladesh Journal of Pharmacology, 2019)
The present study investigates the effect of ludartin on spinal cord injury in rat model. Ludartin treatment decreased the expression of myeloperoxidase and malondialdehyde in spinal cord tissues. The expression of glutathione and superoxide dismutase were enhanced. It also exhibited inhibitory effect on reduction of NeuN-positive cells. The proportion of TUNEL positive cells was also regulated. In addition, ludartin treatment prevented the onset of apoptosis which was evident by decrease in caspase-3 and Bax level and increase of Bcl‑2 level. Up-regulation of tumor necrosis factor‑α, inter-leukin‑1β and I interleukin‑6 by spinal cord injury was suppressed by ludartin treatment. There was improvement in locomotion of rats by treatment with ludartin. Ludartin treatment of spinal cord injury rats improves locomotion by inhibiting inflammatory cytokine expression and preventing cell apoptosis. Thus, ludartin has therapeutic importance in spinal cord injury treatment. Video Clip of Methodology: 3 min 35 sec: Click to watch